Preparation of Financial Statements for the Palm Oil Trading Business at CV. Zhafran Jaya Based on Financial Accounting Standards for Micro, Small, and Medium Entities - Yestin Aprilia; Nini Sumarni (Peneliti.net, 2026)
The contribution of Micro, Small, and Medium Enterprises (MSMEs) to the national economy is undeniable. However, on the other hand, the majority of these business actors still face challenges in financial management practices. The lack of a well-structured financial management system often hinders their business growth and operational professionalism. In response to this issue, the government, through the authorized institutions, has issued the Financial Accounting Standards for Micro, Small, and Medium Entities as a guideline for preparing standardized financial statements. Unfortunately, the implementation of these standards has not been evenly adopted. As observed in the case of CV. Zhafran Jaya, the business has not yet implemented SAK EMKM in its financial reporting practices. Based on this condition, this study aims to identify all financial transaction activities of CV. Zhafran Jaya and subsequently prepare financial statements in accordance with the principles of SAK EMKM. This study employed a descriptive qualitative approach, with the research conducted at CV. Zhafran Jaya located in Tanjung Pucuk Village, Jambi Province. Data collection techniques involved in-depth interviews with the business owner, supported by document reviews and field observations to obtain comprehensive primary data. The findings indicate that the financial recording system of CV. Zhafran Jaya remains conventional and highly simplistic. Financial records are limited only to cash inflows and outflows, without the application of double-entry bookkeeping, account classification, or proper journal preparation. Furthermore, the business has never prepared formal financial statements based on SAK EMKM standards. After reconciliation and reconstruction of the financial statements in accordance with the standards, the company was found to generate a net profit of IDR 146,487,600, while its total assets amounted to IDR 3,415,561,765.